A method of electron beam induced synthesis of metal organic framework materials
By treating the precursor mixture of metal salt, organic ligand, and solvent with electron beam irradiation, the problems of long reaction time and high energy consumption in MOF material synthesis were solved, and rapid and controllable MOF material synthesis was achieved.
Patent Information
- Application Number
- CN202611463225.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-11-03
AI Technical Summary
Existing methods for synthesizing MOF materials involve long reaction times, high energy consumption, and difficulty in rapidly controlling the nucleation process. Traditional solvothermal methods are greatly affected by temperature, concentration, solvent, and reaction time.
A method for synthesizing metal-organic framework materials using electron beam induction was developed. This method involves treating a precursor mixture of metal salt, organic ligand, and solvent with electron beam irradiation to promote the coordination assembly of metal nodes and organic ligands, thereby achieving rapid synthesis.
Rapid synthesis of MOF materials has been achieved with short reaction time, low temperature, and simple equipment operation. Furthermore, the crystal phase composition, crystallinity, grain size, and crystalline/amorphous structure of the product can be controlled by the irradiation dose.
Smart Images

Figure CN123026801A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal-organic framework material preparation technology, and in particular to a method for electron beam-induced synthesis of metal-organic framework materials. Background Technology
[0002] Metal-organic frameworks (MOFs) are a class of crystalline porous materials formed by the coordination bonds between metal ions or metal clusters and organic ligands. Due to their designable structures, tunable pore structures, and diverse compositions, MOFs have attracted widespread attention in fields such as adsorption separation, catalysis, sensing, ion conduction, and energy materials.
[0003] ZIF-62 is a zeolite imidazole ester framework material constructed from zinc ions and a mixture of imidazole and benzimidazole ligands. Compared with some traditional MOF materials, ZIF-62 has the characteristics of a mixed ligand structure and the ability to undergo crystalline-amorphous transitions, making it an important model system for studying MOF structure regulation and amorphous MOF materials. MIL-88B(Fe) and MIL-53(Fe) are iron-based metal-organic framework materials constructed from iron ions and terephthalic acid ligands, possessing typical ferrite cluster or ferrite chain structural units, and are important representatives of iron-based MOFs.
[0004] Currently, the synthesis of the aforementioned MOF materials mainly relies on methods such as solvothermal, hydrothermal, microwave, ultrasonic, or room temperature precipitation. However, traditional solvothermal methods typically require high temperatures, long reaction times, and closed reactor conditions; furthermore, the nucleation and growth processes of the products are significantly affected by temperature, concentration, solvent, and reaction time. Therefore, developing a fast, tunable, and controllable method for preparing MOF nucleation processes is of great significance. Summary of the Invention
[0005] The purpose of this invention is to provide a method for electron beam-induced synthesis of metal-organic framework materials. This method has a fast reaction rate, adjustable conditions, and external field control of the MOF nucleation process, which solves the problems of long reaction time, high energy consumption, and difficulty in rapid control of the nucleation process in traditional MOF synthesis methods.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for electron beam-induced synthesis of metal-organic framework materials, comprising the following steps: Metal salt, organic ligand and solvent are mixed to obtain precursor mixture; The precursor mixture was placed in a sealed container and irradiated with an electron beam to obtain a metal-organic framework material. The metal-organic framework material is one of ZIF-62, MIL-88B(Fe) and MIL-53(Fe).
[0007] Preferably, when the metal-organic framework material is ZIF-62, the metal salt is a zinc salt, the organic ligand includes imidazole and benzimidazole, and the solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, methanol, and ethanol.
[0008] Preferably, the zinc salt is Zn(NO3)2·6H2O, the molar ratio of imidazole to benzimidazole is 4~10:1, and the molar ratio of the organic ligand to the zinc element in the zinc salt is 3~8:1.
[0009] Preferably, when the metal-organic framework material is MIL-88B(Fe), the metal salt is a ferric salt, the organic ligand is terephthalic acid, and the molar ratio of Fe to terephthalic acid in the ferric salt is 1:1 to 4:3; the solvent is one or more of N,N-dimethylformamide, water, and ethanol.
[0010] Preferably, when the metal-organic framework material is MIL-53(Fe), the metal salt is a ferric salt, the organic ligand is terephthalic acid, and the molar ratio of Fe to terephthalic acid in the ferric salt is 1:1; the solvent is N,N-dimethylformamide, or the solvent is water and N,N-dimethylformamide.
[0011] Preferably, the sealed container is an aluminum foil bag or a polyethylene bag; the thickness of the liquid layer formed by the precursor mixture in the sealed container is 0.1~20 mm.
[0012] Preferably, the energy of the electron beam is 0.5~5MeV and the irradiation dose is 50~1500KGy.
[0013] Preferably, after completing the irradiation treatment, the product is further subjected to solid-liquid separation, washing and drying in sequence to obtain a metal-organic framework material.
[0014] Preferably, the drying temperature is 40~120℃ and the time is 12~24 h.
[0015] This invention provides a method for electron beam-induced synthesis of metal-organic framework (MOF) materials. The method involves mixing a metal salt, an organic ligand, and a solvent to obtain a precursor mixture. This precursor mixture is then placed in a sealed container and irradiated with an electron beam to induce a coordination reaction between the metal ions and the organic ligand, yielding the MOF material. This invention activates the solvent and precursor system through electron beam irradiation, promoting the coordination and assembly of metal nodes with organic ligands, thus achieving rapid synthesis of MOF materials. Compared to traditional solvothermal methods, the method provided by this invention features shorter reaction time, lower temperature, simpler equipment operation, and the ability to control the crystal phase composition, crystallinity, grain size, defect degree, and crystalline / amorphous structural state of the product through irradiation dosage.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses an electron beam as an external field energy input (a non-traditional energy input method), which can induce the nucleation and coordination assembly of MOF precursor systems in a short time, thereby inducing the rapid synthesis of MOF materials.
[0017] (2) The present invention regulates the formation process of ZIF-62, MIL-88B(Fe) and MIL-53(Fe) by adjusting the electron beam dose, ligand ratio, metal salt type and solvent system.
[0018] (3) The method of the present invention has simple operation steps and can avoid the problem of long-term high-temperature reaction in traditional solvothermal methods, providing a new technical route for the rapid synthesis of MOF materials. Attached Figure Description
[0019] Figure 1 The image shows the XRD pattern of ZIF-62 synthesized by electron beam in Example 1. Figure 2 The image shows the XRD pattern of MIL-88B(Fe) synthesized by electron beam in Example 2. Figure 3 The image shows the XRD patterns of MIL-53(Fe) synthesized by electron beam under different irradiation doses in Example 3. Detailed Implementation
[0020] In this invention, unless otherwise specified, the raw materials or reagents required for preparation are all commercially available products well known to those skilled in the art.
[0021] This invention provides a method for electron beam-induced synthesis of metal-organic framework materials, comprising the following steps: Metal salt, organic ligand and solvent are mixed to obtain precursor mixture; The precursor mixture was placed in a sealed container and irradiated with an electron beam to obtain a metal-organic framework material. The metal-organic framework material is one of ZIF-62, MIL-88B(Fe) and MIL-53(Fe).
[0022] In this invention, when the metal-organic framework material is ZIF-62, the metal salt is preferably a zinc salt, the organic ligand preferably includes imidazole and benzimidazole, and the solvent is preferably one or more of N,N-dimethylformamide, N,N-dimethylacetamide, methanol, and ethanol. When the solvent is two or more of the above, this invention does not have a special limitation on the ratio of different types of solvents, and any ratio is acceptable.
[0023] In this invention, when the metal-organic framework material is ZIF-62, the zinc salt is preferably Zn(NO3)2·6H2O, the molar ratio of imidazole to benzimidazole is preferably 4~10:1, more preferably 6~8:1; the molar ratio of the organic ligand to the zinc element in the zinc salt is preferably 3~8:1, more preferably 5~6:1.
[0024] In this invention, when the metal-organic framework material is MIL-88B(Fe), the metal salt is preferably a ferric salt, the organic ligand is preferably terephthalic acid, and the ferric salt is preferably FeCl3·6H2O; the molar ratio of Fe to terephthalic acid in the ferric salt is preferably 1:1 to 4:3, more preferably 1:1; the solvent is preferably one or more of N,N-dimethylformamide, water, and ethanol. When the solvent is two or more of the above, this invention does not have a special limitation on the ratio of different types of solvents, and any ratio is acceptable.
[0025] When the metal-organic framework material is MIL-88B(Fe), the raw material mixing process preferably further includes the addition of glacial acetic acid. The molar ratio of glacial acetic acid to Fe in the ferric salt is preferably 0-20:1, more preferably 5.83:1. This invention uses acetic acid as a monocarboxylic acid regulator / competitive coordinating agent to regulate Fe content. 3+ The coordination assembly process between terephthalic acid and terephthalic acid.
[0026] In this invention, when the metal-organic framework material is MIL-53(Fe), the metal salt is preferably a ferric salt, and the organic ligand is preferably terephthalic acid; the ferric salt is preferably FeCl3·6H2O; the molar ratio of Fe to terephthalic acid in the ferric salt is preferably 1:1; the solvent is preferably N,N-dimethylformamide, or the solvent is preferably water and N,N-dimethylformamide, and the volume ratio of water to N,N-dimethylformamide is preferably 1:0 to 1:5 and not 0.
[0027] When the metal-organic framework material is MIL-53(Fe), electron beam irradiation treatment preferably includes a selective heating aging step to obtain the MIL-53(Fe) material; the heating aging temperature is preferably 60°C, and the heating time is preferably 12 hours. This invention can promote further coordination rearrangement of the Fe-BDC precursor formed after electron beam irradiation through heating aging, thereby improving the crystallinity and phase purity of MIL-53(Fe).
[0028] The present invention does not impose a uniform ratio on the amount of solvent used. The amount of solvent used is sufficient to fully dissolve or uniformly disperse the metal salt and organic ligand, and to form a thin liquid layer in the resulting precursor mixture in a sealed container. The specific amount of solvent used for different material systems is shown in the various embodiments.
[0029] The present invention does not impose any special limitations on the specific process of mixing the metal salt, organic ligand and solvent; the mixture can be mixed evenly according to a process known in the art.
[0030] In this invention, the sealed container is preferably an aluminum foil bag or a polyethylene bag; the thickness of the liquid layer formed by the precursor mixture in the sealed container is preferably 0.1~20 mm, more preferably 1~5 mm.
[0031] The present invention does not have any special limitation on the source of the sealed container; the above-mentioned commercially available products known in the art are acceptable.
[0032] In this invention, the energy of the electron beam is preferably 0.5~5MeV, more preferably 1~1.8MeV; the irradiation dose is preferably 50~1500KGy, more preferably 200~1000KGy, further preferably 500~800KGy, and even more preferably 600~700KGy. The irradiation dose of the electron beam is adjusted according to the type of target MOF material and the concentration of the precursor. If the irradiation dose is too low, the system cannot fully nucleate; if the irradiation dose is too high, it may cause damage to the organic ligands or disorder of the framework. Therefore, the above-mentioned range of electron beam irradiation dose is limited.
[0033] When an electron beam acts on a precursor system containing solvent, metal salt, and organic ligand, it can induce the solvent molecules or reactants to generate free radicals, active intermediates, or locally highly activated environments, thereby promoting the deprotonation of organic ligands and the coordination assembly between metal ions and ligands.
[0034] In this invention, electron beam irradiation is preferably performed at room temperature, and the irradiation endpoint is defined as the cumulative absorbed dose measured by a dosimeter reaching a specified electron beam irradiation dose.
[0035] In this invention, after the irradiation treatment is completed, it is preferable to further perform solid-liquid separation, washing and drying of the obtained product in sequence to obtain a metal-organic framework material.
[0036] In this invention, the solid-liquid separation method is preferably centrifugation, filtration, or static separation; after solid-liquid separation, the solid product is collected and washed sequentially with the organic solvent used in the reaction and a low-boiling-point solvent; the low-boiling-point solvent is preferably one or more of methanol, ethanol, and acetone.
[0037] In this invention, the drying temperature is preferably 40~120℃, more preferably 80~100℃, and the drying time is preferably 12~24 h, more preferably 12~16 h.
[0038] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0039] Unless otherwise specified, the experimental methods described in the various embodiments of this invention are conventional methods; unless otherwise specified, the raw materials used are all commercially available products, and the proportions are all by mass percentage.
[0040] Example 1
[0041] Electron beam-induced synthesis of ZIF-62: Weigh 134.0 mg (0.45 mmol) Zn(NO3)2·6H2O and ligands (136.0 mg (2 mmol) imidazole and 30.0 mg (0.25 mmol) benzimidazole, with a molar ratio of 8:1) according to a stoichiometric ratio of 1:5. Add 5 mL of N,N-dimethylformamide and mix thoroughly. Seal the resulting precursor mixture in an aluminum foil bag, remove any obvious air bubbles, and seal it to form a 1 mm thick liquid layer. Irradiate the mixture with an electron beam at an energy of 1.8 MeV and an electron beam irradiation dose of 700 KGy. The irradiation endpoint is defined as the cumulative absorbed dose reaching the specified electron beam irradiation dose value as measured by a dosimeter. After irradiation, let the reaction product stand at room temperature for 12 h, then centrifuge to collect the solid product. Wash the solid product three times with N,N-dimethylformamide and three times with ethanol. Dry the solid product under vacuum at 80 °C for 12 h to obtain ZIF-62 material.
[0042] Example 2
[0043] Electron beam-induced synthesis of MIL-88B(Fe): Weigh 810 mg (3 mmol) of FeCl3·6H2O and 498 mg (3 mmol) of terephthalic acid according to a stoichiometric ratio of 1:1. Add 30.0 mL of N,N-dimethylformamide (DMF) and 0.5 mL of deionized water, and add 1.0 mL (17.5 mmol) of glacial acetic acid as a coordination modifier. Stir until homogeneous, seal the resulting precursor mixture in an aluminum foil bag, remove any obvious air bubbles, and seal again to form a 1 mm thick liquid layer. Irradiate the mixture with an electron beam at an energy of 1.8 MeV and an irradiation dose of 1000 KGy. The irradiation endpoint is defined as the cumulative absorbed dose reaching the specified electron beam irradiation dose value as measured by a dosimeter. Collect the solid product after irradiation by centrifugation, wash three times with DMF and three times with ethanol, and dry at 60 °C for 12 h to obtain MIL-88B(Fe) material.
[0044] Example 3
[0045] Electron beam-induced synthesis of MIL-53(Fe): Weigh 810.9 mg FeCl3·6H2O and 498.4 mg terephthalic acid according to a stoichiometric ratio of 1:1, add them to 15 mL of N,N-dimethylformamide, and then ultrasonically disperse the resulting precursor mixture. Seal the mixture in an aluminum foil bag, remove any obvious air bubbles, and seal it again to form a 1 mm thick liquid layer. Irradiate the mixture with an electron beam at an energy of 1.8 MeV. The irradiation doses are 500 KGy, 700 KGy, and 900 KGy, respectively. The irradiation endpoint is defined as the cumulative absorbed dose measured by a dosimeter reaching the specified electron beam irradiation dose. After irradiation, allow the mixture to stand at room temperature for 12 h, then centrifuge to collect the solid product. Wash the solid product three times with DMF, then replace it with methanol three times, and dry it at 60 °C for 12 h to obtain three MIL-53(Fe) materials with different irradiation doses.
[0046] Characterization
[0047] Figure 1 The image shows the XRD pattern of ZIF-62 synthesized by electron beam in Example 1; as shown. Figure 1 As shown, the positions and relative intensities of the main diffraction peaks of the obtained sample are basically consistent with the simulated XRD pattern of black ZIF-62, and no other obvious characteristic peaks of crystal phases were observed, indicating that the obtained sample formed the characteristic crystal structure of ZIF-62, indicating that ZIF-62 material was successfully prepared by the electron beam irradiation method described in this invention.
[0048] Figure 2 The image shows the XRD pattern of MIL-88B(Fe) synthesized by electron beam in Example 2; as shown. Figure 2As shown, the positions of the main diffraction peaks of the obtained sample are basically consistent with the simulated XRD pattern of black MIL-88B(Fe), indicating that the obtained product has the characteristic crystal structure of MIL-88B(Fe). This demonstrates that the electron beam irradiation method described in this invention can successfully induce the coordination assembly of Fe ions with terephthalic acid ligands to prepare MIL-88B(Fe) material.
[0049] Figure 3 The XRD patterns of MIL-53(Fe) synthesized by electron beam under different irradiation doses in Example 3 are shown below. Figure 3 As shown, the main characteristic diffraction peaks of the obtained sample are basically corresponding in peak position to the simulated XRD pattern of black MIL-53(Fe), indicating that the obtained product has the characteristic crystal structure of MIL-53(Fe), and that the framework MIL-53(Fe) material was successfully prepared by the electron beam irradiation method described in this invention.
[0050] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for electron beam-induced synthesis of metal-organic framework materials, characterized in that, Includes the following steps: Metal salt, organic ligand and solvent are mixed to obtain precursor mixture; The precursor mixture was placed in a sealed container and irradiated with an electron beam to obtain a metal-organic framework material. The metal-organic framework material is one of ZIF-62, MIL-88B(Fe) and MIL-53(Fe).
2. The method according to claim 1, characterized in that, When the metal-organic framework material is ZIF-62, the metal salt is a zinc salt, the organic ligand includes imidazole and benzimidazole, and the solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, methanol, and ethanol.
3. The method according to claim 2, characterized in that, The zinc salt is Zn(NO3)2·6H2O, and the molar ratio of the imidazole and benzimidazole is 4~10:1; the molar ratio of the organic ligand to the zinc element in the zinc salt is 3~8:
1.
4. The method according to claim 1, characterized in that, When the metal-organic framework material is MIL-88B(Fe), the metal salt is a ferric salt, the organic ligand is terephthalic acid, and the molar ratio of Fe to terephthalic acid in the ferric salt is 1:1 to 4:3; the solvent is one or more of N,N-dimethylformamide, water, and ethanol.
5. The method according to claim 1, characterized in that, When the metal-organic framework material is MIL-53(Fe), the metal salt is a ferric salt, the organic ligand is terephthalic acid, and the molar ratio of Fe to terephthalic acid in the ferric salt is 1:1; the solvent is N,N-dimethylformamide, or the solvent is water and N,N-dimethylformamide.
6. The method according to claim 1, characterized in that, The sealed container is an aluminum foil bag or a polyethylene bag; the thickness of the liquid layer formed by the precursor mixture in the sealed container is 0.1~20 mm.
7. The method according to claim 1, characterized in that, The energy of the electron beam is 0.5~5MeV, and the irradiation dose is 50~1500KGy.
8. The method according to claim 1, characterized in that, After the irradiation treatment is completed, the resulting product is then subjected to solid-liquid separation, washing, and drying to obtain a metal-organic framework material.
9. The method according to claim 8, characterized in that, The drying temperature is 40~120℃, and the time is 12~24h.
